CHEMICAL COMPOSITION AND HYDRAULIC CONNECTIVITY OF SPRINGS IN THE SOUTHERN SLOPE OF MERAPI VOLCANO - Johnny Boulom; Doni Prakasa Eka Putra; Wahyu Wilopo (Geological Engineering Department Universitas Gadjah Mada, 2015)
Springs are easily found in the southern slope of Merapi volcano, Sleman Regency, Yogyakarta Special Province, Indonesia. Springs origins on this location are commonly related to the existing of Merapi Aquifer System, but importance question of all these springs are hydraulic connectivity among them. In response to the issue, the objective of this research is to determine hydraulic connectivity of springs based on their chemical composition. To answer the objectives, measurement of spring discharge and physicochemical properties of spring’s water and sampling of selected spring’s water were conducted on this research in the study area. Water chemistry composition was classify by Kurlov formula and displayed by Fingerprint diagram and Composition diagram. Results show that the chemical compositions of most all spring samples are almost similar and does not significantly different for most properties from upstream to downstream, which are Na–Ca–HCO3 water, only one spring of Umbul Jatiningsih spring had different chemical composition of Ca–Na–Mg– HCO3 water. Based on the Fingerprint diagram and Composition diagram evaluation, the spring’s water can be differentiated into three groups. Group 1 consists of ten springs which have similar chemical composition of Na–Ca–HCO3 and with electrical conductivity ranges between 150 to 200 mS/cm. Group 2 consists only one spring “Umbul Pajangan” which contain similar chemical composition to Group 1 but has significantly higher ions concentration (EC value about 400 mS/cm) and Group 3 consists also only one spring “Umbul Jatiningsih” which has significantly different ionic composition with Group 1 and 2. Regarding on this condition, it can be concluded that Group 1 spring is hydraulically connected and relate to the shallow aquifer system of Merapi Aquifer System. In other side, water of spring “Umbul Pajangan”possibly comes from deeper aquifer system of Merapi Aquifer System and this argument is supported by the spring discharge evaluation. Finally, spring “Umbul Jatiningsih” is originate mainly from different aquifer system of porous limestone aquifer. Keywords: Merapi aquifer system, spring, chemical composition, geological condition